Left Ventricular Relative Wall Thickness Versus Left Ventricular Mass Index in Non-Cardioembolic Stroke Patients. Issue 20 (May 2015) - Hashem, M-Sherif; Kalashyan, Hayrapet; Choy, Jonathan; Chiew, Soon K.; Shawki, Abdel-Hakim; Dawood, Ahmed H.; Becher, Harald; Suárez., Alejandro López
<x xml:space="preserve">Abstract</x> Abstract In non-cardioembolic stroke patients, the cardiac manifestations of high blood pressure are of particular interest. Emerging data suggest that echocardiographically determined left ventricular hypertrophy is independently associated with risk of ischemic stroke. The primary objective of this study was to evaluate the frequency of different patterns of left ventricular (LV) remodeling and hypertrophy in a group of consecutive patients admitted with non-cardioembolic stroke or transient ischemic attack (TIA). In particular, we were interested in how often the relative wall thickness (RWT) was abnormal in patients with normal LV mass index (LVMI). As both abnormal RWT and LVMI indicate altered LV remodeling, the secondary objective of this research was to study whether a significant number of patients would be missing the diagnosis of LV remodeling if the RWT is not measured. All patients were referred within 48 hours after a stroke or a TIA for a clinically indicated transthoracic echocardiogram. The echocardiographic findings of consecutive patients with non-cardioembolic stroke or TIA were analyzed. All necessary measurements were performed in 368 patients, who were enrolled in the study. Mean age was 63.7 ± 12.5 years, 64.4% men. Concentric remodeling carried the highest frequency, 49.2%, followed by concentric hypertrophy, 30.7%, normal pattern, 15.5%, and eccentric hypertrophy, 4.1%. The frequency of abnormal left ventricular RWT (80.4%) was significantly higher than that of abnormal LVMI (35.3%), (McNemar P < 0.05). In this group of non-cardioembolic stroke patients, abnormal LV remodeling as assessed by relative wall thickness is very frequent. As RWT was often found without increased LV mass, the abnormal left ventricular geometry may be missed if RWT is not measured or reported.